Recombinant Human Regenerating Gene 4 Attenuates the Severity of Osteoarthritis by Promoting the Proliferation of Articular Chondrocyte in an Animal Model - Li, Xue-jia; Zhu, Fei; Li, Bo; Zhang, Dong; Liang, Cheng-Wei (Current Molecular Pharmacology, 2022)
Introduction: Osteoarthritis (OA) is a dominant cause of morbidity and disability. As a chronic disease, its etiological risk factors and most therapies at present, are empirical and symptomatic. Regenerating gene 4 (Reg4) is involved in cell growth, survival, regeneration, adhesion, and resistance to apoptosis, which are partially thought to be the pathogenic mechanisms of OA. However, the proper role of Reg4 in OA is still unknown. Methods: In this study, a consecutive administration of rhReg4 was applied to normal Sprague- Dawley rats or rats after OA induction. Histological changes and chondrocyte proliferation in the articular cartilage were measured. Results: We found that RhReg4 promotes chondrocyte proliferation in normal rats, and RhReg4 attenuated the severity of OA in rats by promoting chondrocytes’ proliferation in OA rats. Conclusion: In conclusion, recombinant human regenerating gene 4 (rhReg4) attenuates the severity of osteoarthritis in OA animal models and may be used as a new method for the treatment of osteoarthritis.
Keywords: rats